Limb-Kinetic apraxia of legs in Parkinson’s disease: Prospective clinical investigation - Yacov Balash; Evelin D. Mate; Riyad Idries; Anda Eilam; Amos D. Korczyn (Clinical Parkinsonism & Related Disorders)
Background: The study of dynamic organization of motor acts is important for investigation of motor impairment, and a possible sign of a disorder of fronto-parietal areas of the brain in Parkinson’s disease (PD). We aimed to prospectively investigate whether limb-kinetic apraxia in legs (LKA-L) is a heretofore unrecognized manifestation of PD independent of bradykinesia and rigidity. Methods: Patients with PD and healthy controls (HC) performed bipedal reciprocal coordination (BRC) and monopedal reciprocal coordination (MRC) tests as a foot modification of the Oseretzky exam (originally alternate antiphase clenching and unclenching of the fists of the right and left hands). While MRC allowed for alternating movements of one leg per unit of time, BRC required synchronous movements of both legs in antiphase. Leg movement rates and their quality were measured by video recording and compared statistically between the groups of PD and HC. Results: The cohort consisted of 31 PD patients (mean age 69.3 ± 7.1 years,16 males) and 12 HC (mean age 69 ± 6.2 years, 6 males). No differences between PD and HC groups were identified in MRC rate of performance, which were used as a measure of legs movement speed, although the quality of MRC movements was poorer in PD patients (p = 0.022). BRC rate and its performance quality were significantly flawed in PD compared to controls (P = 0.002 and P = 0.003, respectively). Conclusions: Testing for dynamic organization of LKA-L revealed disorder in individuals with PD. LKA-L analyses should be considered in the diagnosis of leg movements and gait disorders in PD.